2008
DOI: 10.1002/hc.20488
|View full text |Cite
|
Sign up to set email alerts
|

Organotin(IV) esters of (E)‐3‐furanyl‐2‐phenyl‐2‐propenoic acid: Synthesis, investigation of the coordination modes by IR, multinuclear NMR (1H, 13C, 119Sn) and In Vitro biological studies

Abstract: Complexes [Me2SnL2 (I), Me3SnL (II), Et2SnL2 (III), n‐Bu2SnL2 (IV), n‐Bu3SnL (V), n‐Oct2SnL2 (VI)], where L is (E)‐3‐furanyl‐2‐phenyl‐2‐propenoate, have been synthesized and structurally characterized by vibrational and NMR (1H, 13C and 119Sn) spectroscopic techniques in combination with mass spectrometric and elemental analyses. The IR data indicate that in both the di‐ and triorganotin(IV) carboxylates the ligand moiety COO acts as a bidentate group in the solid state. The 119Sn NMR spectroscopic data, 1J[11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Several organotin(IV) compounds have also been shown to exhibit important cytotoxic effects, and their activities are investigated as possible antitumor compounds. Organotin(IV) carboxylates, particularly, merit special attention because of their antitumor [4] and antibacterial activities . It is worthwhile to highlight that organotin(IV) compounds are commercially utilized as biocidally active agents .…”
Section: Introductionmentioning
confidence: 99%
“…Several organotin(IV) compounds have also been shown to exhibit important cytotoxic effects, and their activities are investigated as possible antitumor compounds. Organotin(IV) carboxylates, particularly, merit special attention because of their antitumor [4] and antibacterial activities . It is worthwhile to highlight that organotin(IV) compounds are commercially utilized as biocidally active agents .…”
Section: Introductionmentioning
confidence: 99%
“…1 J C69/71Ga of 182 Hz/232 Hz and 1 J C115In ¼ 310710 Hz couplings have been determined by Wrackmeyer and Klimkina 87 for lithium tetra(tertbutyl)gallate and -indate, respectively; DFT calculations at the B3LYP/ 6-311 þ G(d,p) level of theory have been performed by the authors for tri(tert-butyl)gallium, trimethylgallium and tetramethylgallate in order to predict 1 J CGa couplings. 1 J CSn and 2 J HSn couplings measured by Sadiq-ur-Rehman et al 88 for organotin(IV) esters of (E)-3-furanyl-2-phenyl-2-propenoic acid indicated a four-coordinated environment around the tin atom in triorganotin(IV) and five-coordinated in diorganotin(IV) carboxylates in non-coordinating solvents. The 1 J CSn couplings of about 325 to 363 Hz measured for organotin(IV) derivatives of 4-[(2,4-dinitrophenyl)amino)]-4-oxo-2-butenoic acid and 2-{[(2,4-dinitrophenyl)amino)]carbonyl}benzoic acid indicate that the tin atom in the compounds studied is four-coordinated in solution.…”
Section: One-bond Couplings Not Involving Hydrogenmentioning
confidence: 90%
“…Upon treatment of these two acids with organotin oxide or organotin hydroxide in anhydrous benzene, a series of triorganotin (4H-1,2,4-triazol-4-yl)benzoates were obtained (Scheme 2), which have been characterized by IR and NMR ( 1 H, 13 C, and 119 Sn) spectra as well as elemental analyses.…”
Section: Synthesis and Characterization Of Complexesmentioning
confidence: 99%
“…Among these organotin derivatives, organotin carboxylates have attracted extensive attention because of their versatile structures [1,2] as well as significant biological activities [3][4][5], especially anticancer activity [6]. In recent years, more and more investigations have focused on the synthesis of organotin carboxylates of functionalized carboxylic acids with additional O, S, or N donor groups [7][8][9][10][11][12][13]. Owing to the presence of additional coordinating atoms, these organotin carboxylates show considerable structural diversity.…”
Section: Introductionmentioning
confidence: 99%